Public Opinion Research Is A Factor In Maintaining Social Stability (Czech Journal of Multidisciplinary Innovations, 2024)
Studying public opinion and developing strategic systems to conduct these processes systematically is a crucial task today. It is equally important to strengthen political, philosophical, psychological, and sociological research within society